Geometrical instability in the imbibition of a sphere. Issue 37 (30th August 2016) - Debacker, Alban; Lootens, Didier; Hébraud, Pascal
Abstract : We study the imbibition of a spherical porous aggregate. Abstract : We study the imbibition of a spherical porous aggregate. When the difference in pressure between the inside and the outside of the aggregate is large enough, the imbibition front becomes unstable. This instability leads to the acceleration of the imbibition process. In more complex geometries with non-constant curvatures, the imbibition becomes locally unstable in the regions with the highest curvatures, leading to spatially heterogeneous front velocities.